Taxonomic identity of Torenia leucosiphon (Linderniaceae) and its resurrection from the synonymy of Torenia travancorica - Prasad, Mangavayal Govindan; Sunojkumar, Purayidathkandy (Phytotaxa, 2015)
Taxonomic identity of Torenia leucosiphon is discussed. Perusal of literature shows that it has been treated as a synonym of Torenia travancorica. However, a detailed analysis of the type, additional specimens and protologue information of both taxa clearly indicates that T. leucosiphon should be treated as a distinct species. Therefore, T. leucosiphon is resurrected from the synonymy of T. travancorica and recognised as an independent species. Lectotypes of T. leucosiphon and T. travancorica were also designated. Detailed description, illustration, colour photographs, distribution and habitat notes of both T. travancorica and T. leucosiphon are provided along with a key to the Southern Peninsular Indian species of the genus Torenia.